(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the studying results and establishing the cultivation and planting methods influence of new varieties of potatoes. It was revealed that the large-tuber new varieties cultivation of potatoes in an early and two-yielding culture with a two-line planting method (90 + 30x22cm) with 74 thousand / ha density contributes to obtaining the highest yield (25.8-47.0 t / ha) with 3.1 -4.8 reproduction factor. At the same time, the marketable tubers yield amounted to 34.6-46.5 t / ha (spring planting) and 24.6-34.4 t / ha (summer planting). The mid-early varieties Arizona, Yarokli-2010 and Bogizogon differed in yield, marketability, and multiplication rate.